2022
DOI: 10.1101/2022.09.12.507611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-Modal Representation of Identity in Primate Hippocampus

Abstract: Faces and voices are the dominant social signals used to recognize individuals amongst human and nonhuman primates. Yet, evidence that information across these signals can be integrated into a modality-independent representation of individual identity in the primate brain has been reported only in human patients. Here we show that, like humans, single neurons in the marmoset monkey hippocampus exhibit invariant neural responses when presented with the faces or voices of specific individuals. However, we als… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…The fact that our monkeys learned numerous crossmodal associations should not be surprising since, in nature, monkeys recognize alarm calls about predators (Seyfarth et al, 1980). Moreover, there is evidence that neurons in the monkey's hippocampus respond invariantly to the face and voice of conspecifics in the colony (Tyree et al, 2023).…”
Section: Rhesus Macaques Learn Crossmodal Equivalences Across Paramet...mentioning
confidence: 78%
“…The fact that our monkeys learned numerous crossmodal associations should not be surprising since, in nature, monkeys recognize alarm calls about predators (Seyfarth et al, 1980). Moreover, there is evidence that neurons in the monkey's hippocampus respond invariantly to the face and voice of conspecifics in the colony (Tyree et al, 2023).…”
Section: Rhesus Macaques Learn Crossmodal Equivalences Across Paramet...mentioning
confidence: 78%
“…222 A recent study in marmosets suggests that the hippocampus may be integral to the cross-modal integration of faces and voices for cohesive representations of individual identity. 104 Tyree et al 104 showed that, like humans, 223 individual neurons in the marmoset were highly selective to specific individuals when seeing their faces or hearing their voices.…”
Section: Multimodalitymentioning
confidence: 99%
“…Both macaque 91 and marmoset 90 frontal lobes contain patches of face-selective cells, which are integrated with more extensive face processing and voice processing networks. 85,88,[216][217][218][219][220] Primates match the identity of an individual across their face and voice, 104,221 though data on how these social signals are integrated for social recognition at the neural level are only beginning to emerge. 222 A recent study in marmosets suggests that the hippocampus may be integral to the cross-modal integration of faces and voices for cohesive representations of individual identity.…”
Section: Multimodalitymentioning
confidence: 99%
See 2 more Smart Citations